Gainers and Losers in Priority Services - Gershkov, Alex; Winter, Eyal (Journal of Political Economy, 2023)
We analyze the implications of priority service (PS) on customers’ welfare. In monopoly markets, PS can often decrease consumer surplus and can even yield a loss of welfare to all consumers. This happens despite its efficiency gains, as monopolists levy in revenue more than the total efficiency gains. PS can increase consumer surplus if it expands the consumption coverage—that is, if it introduces new customers who would not purchase the service otherwise. In duopoly markets, the price competition over PS can be severely eroded. Under homogeneity, firms act as if they were monopolists serving half of the market.